SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PENERIMA BANTUAN LANGSUNG TUNAI (BLT) DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) ( Studi Kasus: Desa Sambuli, Kecamatan Abeli, Kota Kendari ) - Reina Rahmona; Ika Purwanti Ningrum; Natalis Ransi (semanTIK, 2016)
As a result of the increase in the price of fuel (fuel oil), the government held a relief for the people of Indonesia, namely direct cash assistance  (BLT).  Indonesian government believes these measures are important for the country's fiscal rescue. At this difficult time, direct cash assistance program be good news for the poor throughout the country. In this study, the criteria used by 5 criteria using AHP method to enter data in the form of the head of the family that was obtained from the Central Statistics Agency kendari city. This decision support system is implemented using the Java programming language integrated with MySQL database. Results of this study states AHP method can be implemented into a decision support system to determine the recipients of direct cash assistance. This system can provide the best receiver making it easier for the government to provide assistance. Keywords— Method of AHP, Decision Support Systems, Cash Direct Assistance Receivers (BLT)